The Morocco-Nigeria BIT: An Important contribution to Ensuring the Accountability of TNCs for Their Human Rights Violations? - Philippa Osim Inyang (European Scientific Journal, ESJ, 2023)
Corporate accountability for human rights violations has been at the forefront of the business and human rights debate. This debate has focused on the establishment of binding human rights obligations on corporate entities, particularly following the Human rights Council’s initiative to establish a treaty on business and human rights– a mandate given to the open-ended intergovernmental working group on transnational corporations and other business enterprises with respect to human rights. Joining this debate, this paper briefly comments on relevant provisions of the 2016 Morocco-Nigeria Bilateral Investment Treaty (BIT) which appears to contain innovative provisions that seek to ensure that investors (who are often corporate entities) are held accountable for their investment activities that adversely impact human rights within their host States. Although the Morocco-Nigeria BIT remains exceptional within the investment treaty framework, it reflects an initiative to ensure that the next generation of BITs encourages greater corporate accountability for their human rights violations.